Microsoft Windows server 2003 administrator's companion - Russel, Charlie (Microsoft Press, 2003)
This comprehensive administrator's reference details operating system features and capabilities and provides easy-to-follow procedures, practical workarounds, and key troubleshooting tactics for on-the-job results with the Windows® Server 2003 family.